Tradycja i redakcja przekazu o pośpiechu Pawła na święta Pięćdziesiątnicy (Dz 20, 16) - Rakocy, Waldemar (The Biblical Annals, 2017)
The note about Paul’s hurry for the day of Pentecost in Acts 20, 16 arouses numerous doubts. Authors think that Luke hides the actual reason while he sailed past Ephesus, for in itself it is paradoxical; the calling of the presbyters at Miletus postponed the journey even more. Studying the redaction in which we find the above note, and then the tradition from which it has stemmed out, make us look at Luke as a reliable narrator of Paul’s itinerary in 20:1-38. The reason why Paul sailed past Ephesus seems to be in accordance with the historical realities.